2013
DOI: 10.1103/physrevb.88.184508
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and magnetism on flux-grown single crystals of NiBi3

Abstract: We present resistivity, magnetization, and specific-heat measurements on flux-grown single crystals of NiBi 3 . We find typical behavior of a type-II superconductor, with, however, a sizable magnetic signal in the superconducting phase. There is a hysteretic magnetization characteristic of a ferromagnetic compound. By following the magnetization as a function of temperature, we find a drop at temperatures corresponding to the Curie temperature of ferromagnetic amorphous Ni. Thus, we assign the magnetism in NiB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…NiBi3 SCs have been studied before. While it has been found that ferromagnetism and superconductivity can coexist in NiBi3 nanostructures [17], ferromagnetism has not been found in bulk single crystals [18][19][20]. In this work, the gap value and symmetry, spin states and T dependence of the gap all demonstrate that the bulk NiBi3 sample is a singlet swave SC.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…NiBi3 SCs have been studied before. While it has been found that ferromagnetism and superconductivity can coexist in NiBi3 nanostructures [17], ferromagnetism has not been found in bulk single crystals [18][19][20]. In this work, the gap value and symmetry, spin states and T dependence of the gap all demonstrate that the bulk NiBi3 sample is a singlet swave SC.…”
Section: Resultsmentioning
confidence: 58%
“…Coexistence of ferromagnetism and superconductivity has been previously observed in NiBi3 nanostructures [17]. But later experiments did not find ferromagnetism in NiBi3 single crystals [18][19][20]. It has also been shown that Bi/Ni bilayers have p-wave triplet superconductivity [42,43].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…12 NiBi 3 is traditionally synthesized by heating Ni and Bi in 1 : 3 ratio at high temperature for several hours/days. Silva et al 13 have synthesized NiBi 3 crystals by heating Ni and Bi in a quartz ampule at 1100 1C for 4 h. They obtained NiBi 3 along with some Ni impurity which shows ferromagnetic behaviour. Esmeralda et al 14 have synthesized impurity Ni free NiBi 3 by heating at 1000 1C for 7 days and have found that NiBi 3 is a type II superconductor which shows ferromagnetism in superconducting phase.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, we measure the lattice parameter of a = 8.15 Å from the real space STM image, as discussed above. Although some early studies indicated the coexistence of superconductivity and ferromagnetism in NiBi 3 [23][24][25] , the recent work reveals that it might be amorphous Ni residuals to bear the responsibility for the magnetic signal 26 . As drawn in Fig.…”
Section: Methodsmentioning
confidence: 98%